2016
DOI: 10.1177/1362361316669088
|View full text |Cite
|
Sign up to set email alerts
|

Drawing the answers: Sketching to support free and probed recall by child witnesses and victims with autism spectrum disorder

Abstract: The success of witness interviews in the criminal justice system depends on the accuracy of information obtained, which is a function of both amount and quality of information. Attempts to enhance witness retrieval such as mental reinstatement of context have been designed with typically developed adults in mind. In this paper, the relative benefits of mental and sketch reinstatement mnemonics are explored with both typically developing children and children with autism. Children watched a crime event video, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 56 publications
2
36
2
Order By: Relevance
“…Most eyewitness studies suggests that, after short delays, children and adults with ASD tend to recall less information than TD peers (Bruck et al, ; Henry, Messer, et al, ; Mattison et al, ; Mattison, Dando, & Ormerod, ; McCrory et al, ; Millward et al, ). However, various studies have also reported that autistic individuals can provide as much correct information about an event as TD peers, especially when appropriate support is given at retrieval (Henry, Crane, et al, ; Maras et al, ; Maras & Bowler, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most eyewitness studies suggests that, after short delays, children and adults with ASD tend to recall less information than TD peers (Bruck et al, ; Henry, Messer, et al, ; Mattison et al, ; Mattison, Dando, & Ormerod, ; McCrory et al, ; Millward et al, ). However, various studies have also reported that autistic individuals can provide as much correct information about an event as TD peers, especially when appropriate support is given at retrieval (Henry, Crane, et al, ; Maras et al, ; Maras & Bowler, ).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the accuracy of the information recalled soon after an event, the research findings are also not consistent, with some suggesting that individuals with ASD are less accurate than non‐ASD peers (e.g., Bruck et al, ; Maras & Bowler, , , ), whereas others have found that they are just as accurate (e.g., Henry, Crane, et al, ; Henry, Messer, et al, ; Maras et al, ; Maras et al, ; Maras & Bowler, ; McCrory et al, ). Still, other researchers have reported that specific interview techniques can help autistic children be as accurate as non‐ASD peers (Mattison et al, , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of children with autism spectrum disorder (henceforth, autism), a small but growing literature indicates that they remember less about witnessed events relative to typically developing (TD) children of comparable age and intelligence (IQ) (Bruck, London, Landa, & Goodman, 2007;McCrory, Henry, & Happe´, 2007), and also when matched for verbal and non-verbal abilities but differing in age (Mattison, Dando, & Ormerod, 2016. Nevertheless, the information that they do provide is often just as accurate (Bruck et al, 2007;Mattison et al, 2015Mattison et al, , 2016 [true for probed but not free recall]; McCrory et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the information that they do provide is often just as accurate (Bruck et al, 2007;Mattison et al, 2015Mattison et al, , 2016 [true for probed but not free recall]; McCrory et al, 2007). Further, children with autism are no more suggestible than their TD peers, and are not more likely to confabulate items of information (Bruck et al, 2007;Mattison et al, 2016Mattison et al, , 2015McCrory et al, 2007).…”
Section: Introductionmentioning
confidence: 99%